To Approach or to Avoid? Motivation Differentially Mediates the Effect of Hardiness on Depressive Symptoms in Chinese Military Personnel. (27th May 2019) - Wang, Xiaoxia; Wong, Janet Yuen-Ha; Zhai, Linkun; Wu, Ruicheng; Huang, Tianhao; He, Renqiang; Xiao, Yang; Yu, Yang; Kong, Xiangji; Zhou, Xiaoyan; Yang, Hui
Abstract : Objective . To investigate the mediation effect of approach/avoidance motivation between hardiness and depressive symptoms. Methods . Cross-sectional design was utilized. Two independent samples of military servicemen (G1: military personnel in the Armed Forces; G2: Chinese army military cadets) (n1 = 98, n2 =140) were sampled and investigated. The assessment tools of hardiness scale (DRS), behavioral activation and inhibition scales (BAS/BIS), and Center for Epidemiological Survey-Depression Scale (CES-D)/Beck Depression Inventory (BDI) were used. General linear model was conducted to examine the predictive role of hardiness (DRS) and motivation (BAS/BIS) on depressive symptoms (CES-D or BDI). The mediating role of BAS/BIS between hardiness and depressive symptoms was examined. Results . (1) Across army soldiers and military medical university cadets, hardiness ( β =-0.394, P <0.001) and behavioral inhibition ( β =0.297, P <0.001) significantly predicted depressive symptoms. (2) For soldiers only, behavioral inhibition mediated the significant association between hardiness and depressive symptoms ( β =-0.043, SE=0.027, 95%CI=-0.130 -0.008). (3) For cadets only, behavioral activation-Drive significantly predicted depressive symptoms ( β =-0.237, P =0.012), and hardiness operates through behavioral activation-Drive to influence depressive symptoms ( β =-0.057, SE=0.036, 95%CI=-0.151 -0.078). Conclusion . Individuals who are low in hardiness and behavioral activation-Drive and who are high in behavioral inhibition showed more severe depressive symptoms. The relationship between hardiness and depressive symptoms was mediated by behavioral activation-Drive in cadets and behavioral inhibition in soldiers. The proposed model offers a useful approach for the development of hardiness training programs to alter approach/avoidance motivation in the military context. Future training program of hardiness could lay more emphasis on promotion of perseverance in pursuing goals in hardy individuals, which may in turn improve active coping.